Invasive histiocytic sarcoma of the lumbar spine in a ferret (Mustela putorius furo). (February 2017) - Warschau, M.; Hoffmann, M.; Dziallas, P.; Hansmann, F.; Baumgärtner, W.; Mischke, R.; Cichowski, S.; Fehr, M.
Abstract : This report describes the history, clinical examination and histopathology of a histiocytic sarcoma in a domestic ferret. Clinical signs were acute paraplegia and dysuria. Physical examination revealed a firm, smooth, touch‐sensitive mass in and around the lumbar vertebral column. Neurologic examination was consistent with a lesion between spinal cord segments T3 and L3. Magnetic resonance images revealed bone lesions of L2 and L3 combined with compression of the spinal cord due to a homogenous, isointense mass that was diagnosed as a malignant round cell tumour and the ferret was euthanased. Histopathology confirmed the diagnosis of an infiltrative histiocytic sarcoma.